Answer:
-4y-2
Step-by-step explanation:
-4(y+1)+2
-4 times y is -4y
-4 times 1 is -4
-4y-4 plus 2
is 4y-2
Answer:
;
is even and greater than zero.
The absolute value function ![y=|x|](https://tex.z-dn.net/?f=y%3D%7Cx%7C)
Step-by-step explanation:
The power function;
;
is even and greater than zero, is symmetric with respect to the positive y-axis.
As
and as ![x\rightarrow -\infty,f(x)\rightarrow \infty](https://tex.z-dn.net/?f=x%5Crightarrow%20-%5Cinfty%2Cf%28x%29%5Crightarrow%20%5Cinfty)
The absolute value function
also has the same end behavior.
The remaining functions in the options provided do not exhibit this end behavior.
See graph in attachment.
Let
N--------> <span>members of the club
we know that
($192/(N+2)=3.20
192=(N+2)*3.20
3.20*N+6.40=192
3.20*N=192-6.40
N=185.60/3.20
N=58
the answer is
58</span>
Answer: y = (1 - 0.527)^t
Step-by-step explanation:
y=e^(-0.75t)
y=(e^-0.75)^t
y= 0.47236655^t
1 - 0.47236655 = 0.52763345
y = (1 - 0.527)^t
Answer:
1
Step-by-step explanation:
(1+sinx)/cosx
(1+sin0)/cos0
(1+0)/1
1/1
1
:. Lim x->0 =1